Efeito do reflorestamento de restingas sobre taxocenose de lagartos - Falcão, Ana Cecília Guedes Pereira (2009)
Habitat loss caused by human occupation and land use has been reducing preserved areas to small and isolated fragments. For a proper management of populations, studies on fauna and flora of primary areas and in successional environment are necessary. In this work, the effect of the reforestation on a soil using lizard assemblage was analyzed in a sandy coastal plain area in northeast of Brazil, during a two year sampling (oct/2006 to may/2008). Samplings were conducted in four reforesting areas 3, 5, 9, and 17 years, and in a control area, in which there was no vegetation removal, with 3 sampling points each, called parcels A, B and C. A line of drift-fences pitfall traps was positioned in each parcel. A total of 768 lizards was collected, representing 13 species of nine families. Richness was similar amongst reforested and control areas, nevertheless, diversity was higher in the latter; on the other hand, individual abundance was higher in the reforested localities. The species composition of lizards differed among reforested and control areas, with differences in dominance and exclusivity of species of each area. The control locality showed higher equitability in the distribution of abundance among species, differently of reforested areas, where there was a predominance of lizards of one or two species. In the control area, two exclusive species were found: Enyalius bibronii e Kentropyx calcarata. On the other hand, both species Cnemidophorus ocellifer e Mabuya heathi were recorded in all reforested areas and absent in the control.